2012
DOI: 10.1083/jcb.201111053
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy genes function sequentially to promote apoptotic cell corpse degradation in the engulfing cell

Abstract: Autophagy genes are not only essential for exposing the engulfment signal on apoptotic cells but also function in phagocytes to promote apoptotic cell removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 26 publications
2
57
1
Order By: Relevance
“…18,19 In the C. elegans epithelial hyp7 cell, we previously observed recruitment of autophagy proteins EPG-5, ATG-18 and LGG-1 to apoptotic cell-containing phagosomes. 23 In C. elegans embryos, however, we failed to see clear association of autophagy proteins such as LGG-1, ATG-5, ATG-3 and ATG-18 with phagosomes. Thus, the regulatory mechanism employed by the autophagy pathway to promote cell corpse degradation in C. elegans embryos is likely different from that in the hyp7 cell or LAP, which only requires part of the autophagy machinery or several autophagy proteins.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…18,19 In the C. elegans epithelial hyp7 cell, we previously observed recruitment of autophagy proteins EPG-5, ATG-18 and LGG-1 to apoptotic cell-containing phagosomes. 23 In C. elegans embryos, however, we failed to see clear association of autophagy proteins such as LGG-1, ATG-5, ATG-3 and ATG-18 with phagosomes. Thus, the regulatory mechanism employed by the autophagy pathway to promote cell corpse degradation in C. elegans embryos is likely different from that in the hyp7 cell or LAP, which only requires part of the autophagy machinery or several autophagy proteins.…”
Section: Discussionmentioning
confidence: 82%
“…However, as loss of ATG-7 (yeast Atg7, human ATG7 ortholog) or UNC-51 (yeast Atg1, human ULK1 ortholog) does not affect cell corpse degradation in the hyp7 cell, these autophagy proteins may act in a manner independent of the conventional autophagy pathway. 23 In a recent report, however, several mutants that affect autophagy at different steps, cause delayed removal of cell corpses in C. elegans embryos, implying that the autophagy process may be involved. 22 Thus, systematic studies are needed to determine whether and how the autophagy pathway regulates apoptotic cell clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that autophagy proteins localize to vesicles containing corpses, allowing for proper processing of dead cells, in a process known as LC3-associated phagocytosis (LAP;Florey et al, 2011;Martinez et al, 2011;. LAP, however, does not appear to require Atg1 or the autophagy initiation process, but does require Atg8 (the Drosophila homolog of LC3) (Florey et al, 2011;Martinez et al, 2011;Li et al, 2012). This is consistent with our findings that knocking down Atg1 but not Atg8 leads to the suppression of corpse accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest, TORC1 has been shown to negatively regulate the initiation of autophagy. Many proteins important in phagosome maturation are shared between both the autophagic and the phagocytic pathways (Martinez et al, 2011;Li et al, 2012). We therefore hypothesized that one of the roles of Drpr may be to act through TORC1 to inhibit the initiation of autophagy and prevent proteins from localizing to autophagosomes when they are needed for phagocytosis.…”
Section: Activating Torc1 In Glial Cells Suppresses Corpse Accumulatimentioning
confidence: 99%
“…For example, abnormalities in larval development, synapse formation, and eye development are observed in autophagy gene mutant Drosophila. [8][9][10][11][12] In C. elegans, autophagy genes play a role in apoptotic corpse clearance in embryonic development, 13 the L1 larval stage, 14 and the adult gonad, 15 in degrading germline P granules in somatic cells, 16 and in the selective elimination of paternal mitochondria. 17,18 In mice, autophagy genes play an essential role in preimplantation development, survival during the neonatal starvation period, and in the differentiation of several specific cell lineages, including adipocytes, erythrocytes, and lymphocytes (T cells and B-1a cells) (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%